2017
DOI: 10.3892/mmr.2017.8232
|View full text |Cite
|
Sign up to set email alerts
|

High expression of FLT3 is a risk factor in leukemia

Abstract: Several studies have shown that internal tandem duplication (ITD) of FMS-like tyrosine kinase 3 (FLT3) can result in the failure of leukemia treatment and contribute to a poor prognosis. However, the role of the overexpression of FLT3 in leukemia remains to be fully elucidated. By mining public database, the present study first identified that the expression of FLT3 in leukemia was markedly higher, compared with that in other types of tumor and cell lines, indicating that FLT3 is important in leukemia. In leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 56 publications
6
43
0
Order By: Relevance
“…Flow cytometry had been recommended as an ideal platform for determination of receptor on cell surface or receptor occupancy . Patients with a high expression of FLT3 , consecutively FLT3 protein expression potentially have higher risk in leukemia . Clear diagnosis consisted of biomarker determination and more intensive drug regimen plan are highly valuable for this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry had been recommended as an ideal platform for determination of receptor on cell surface or receptor occupancy . Patients with a high expression of FLT3 , consecutively FLT3 protein expression potentially have higher risk in leukemia . Clear diagnosis consisted of biomarker determination and more intensive drug regimen plan are highly valuable for this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unsupervised clustering was performed with scRNA-seq data from patient B using the SC3 pipeline (version 1.12.0) (19). The functions of DGEs were determined through a literature review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)…”
Section: Gene Fusion Predictionmentioning
confidence: 99%
“…Supplementation with hypoxanthine, an adenine purine nucleobase derivative that undergoes conversion into the purine nucleotide inosine monophosphate (IMP), was sufficient to significantly reduce the apoptotic effects of quizartinib (Figure 5D).To determine if these findings could be recapitulated in primary human samples, a genetic signature encompassing genes involved in de novo serine synthesis, the one-carbon/folate cycle, and key ratelimiting enzymes of the de novo purine synthesis pathway was devised as described by Manning and colleagues (43) (see also Supplementary Materials and Methods). As FLT3-mutant AMLs have been demonstrated to upregulate FLT3 mRNA expression(49), stratification of the LAML-TCGA dataset by FLT3 mutation status showed a markedly greater, and significant positive correlation between this gene signature and FLT3 mRNA expression in FLT3mutant patient samples (Figure 5E). These data are consistent with the notion that FLT3-ITD inhibition reduces global serine availability and induces nucleotide insufficiency by both suppressing de novo serine synthesis pathway activity and serine uptake.Inhibition of de novo serine synthesis sensitizes FLT3-ITD-driven AMLs to cytarabine Having demonstrated that PHGDH inhibition is a unique metabolic vulnerability in FLT3-ITD-mutant AML, strategies by which PHGDH inhibition could be exploited for the treatment of AML were explored.…”
mentioning
confidence: 94%